Być celebrytą, być paparazzim. Fellini i jego postaci w Słodkim życiu - Godzic, Wiesław (Załącznik Kulturoznawczy, 2022)
In his essay the author discusses the question of film spectator of the particular movie, namely “La Dolce Vita”, directed by Federico Fellini. Since its premiere in February 1960, the movie has produced a lot of controversies, concerning both the artistic aspects, as well as manners and customs. The author concentrates on the extraordinary position of the spectator inside the film narration. He discusses the question of the intertextual place of the viewer both inside the narration and syuzhet. The viewer in many cases plays a role of authors porte parole. The different roles of protagonists are named: fallen aristocrats, petit bourgeois, artists, intellectuals, foreign celebrity. The one of the most important is the role of paparazzi, coined for the first time in the Fellini’s film. It created the aggressive photographer, the “bandit” of the camera. The variety of the roles, with emphasis of the paparazzi, produce the situation, where Fellini brilliantly makes an illusion of fully controlled narration by the spectator. But it is the artistic illusion, nothing more.